Vaccination Against Covid-19: Recommendations for Candidates and Transplant Recipients - Stucchi, Raquel Silveira Bello; Santoro-Lopes, Guilherme; Santos, Daniel Wagner; Abdala, Edson; Clemente, Wanessa Trindade; Pierrotti, Lígia Camera (Brazilian Journal of Transplantation, 2022)
Covid-19 has strongly impacted solid organ transplants (SOT). Patients on the SOT list and those already transplanted belong to the priority population for covid-19 vaccination, which aims to reduce covid-19 morbidity and mortality. All vaccines used today against covid-19 can be administered in the SOT setting. The vaccination schedule (manufacturing platform, age, number of doses, indication of booster doses) varies from country to country.